Mass-selective soft-landing of protein assemblies with controlled landing energies. - Mikhailov, V; Mize, T; Benesch, J; Robinson, C (American Chemical Society, 2014)
Selection and soft-landing of bionanoparticles in vacuum is potentially a preparative approach to separate heterogeneous mixtures for high-resolution structural study or to deposit homogeneous materials for nanotechnological applications. Soft-landing of intact protein assemblies however remains challenging, due to the difficulties of manipulating these heavy species in mass-selective devices and retaining their structure during the experiment. We have developed a tandem mass spectrometer with the capability for controlled ion soft-landing and ex situ visualization of the soft-landed particles by means of transmission electron microscopy. The deposition conditions can be controlled by adjusting the kinetic energies of the ions by applying accelerating or decelerating voltages to a set of ion-steering optics. To validate this approach, we have examined two cage-like protein complexes, GroEL and ferritin, and studied the effect of soft-landing conditions on the method's throughput and the preservation of protein structure. Separation, based on mass-to-charge ratio, of holo- and apo-ferritin complexes after electrospray ionization enabled us to soft-land independently the separated complexes on a grid suitable for downstream transmission electron microscopy analysis. Following negative staining, images of the soft-landed complexes reveal that their structural integrity is largely conserved, with the characteristic central cavity of apoferritin, and iron core of holoferritin, surviving the phase transition from liquid to gas, soft-landing, and dehydration in vacuum.